A color-shifting near-infrared fluorescent aptamer-fluorophore module for live-cell RNA imaging - Zhang, Jingye; Wang, Lu; Jäschke, Andres; Sünbül, Murat (Angewandte Chemie. International edition, 2021)
Fluorescent light-up RNA aptamers (FLAPs) have become promising tools for visualizing RNAs in living cells. Specific binding of FLAPs to their non-fluorescent cognate ligands results in a dramatic fluorescence increase, thereby allowing RNA imaging. Here, we present a color-shifting aptamer-fluorophore system, where the free dye is cyan fluorescent and the aptamer-dye complex is near-infrared (NIR) fluorescent. Unlike other reported FLAPs, this system enables ratiometric RNA imaging. To design the color-shifting system, we synthesized a series of environmentally sensitive benzopyrylium-coumarin hybrid fluorophores which exist in equilibrium between a cyan fluorescent spirocyclic form and a NIR fluorescent zwitterionic form. As an RNA tag, we evolved a 38-nucleotide aptamer that selectively binds the zwitterionic forms with nanomolar affinity. We used this system as a light-up RNA marker to image mRNAs in the NIR region and demonstrated its utility in ratiometric analysis of target RNAs expressed at different levels in single cells.
Gesehen am 29.03.2023